2016
DOI: 10.1111/cas.13084
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of high mobility group box 1 augments antitumor T‐cell response induced by peptide vaccination as a co‐adjuvant

Abstract: High mobility group box 1 (HMGB1) is a member of the family of damage‐associated molecular patterns, which cause inflammation and trigger innate immunity through Toll‐like receptors 2/4 and the receptor for advanced glycation end products. We examined the effect of glycyrrhizin, a selective inhibitor of HMGB1, on the induction of CTLs in mice. B6 mice, either OT‐1 spleen cell‐transferred or untransferred, were immunized with an s.c. injection of OVA 257–264 peptide with topical imiquimod, and glycyrrhizin was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…NM effectively increased the activity of T lymphocytes and natural killer cells in hepatic resection patients (64). Also, NM induced CD8 T-cell proliferation, and played a role as a co-adjuvant for peptide vaccination (65). As mentioned above, the major anti-cancer mechanism of NM was the down-regulation of TNF-α-induced NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%
“…NM effectively increased the activity of T lymphocytes and natural killer cells in hepatic resection patients (64). Also, NM induced CD8 T-cell proliferation, and played a role as a co-adjuvant for peptide vaccination (65). As mentioned above, the major anti-cancer mechanism of NM was the down-regulation of TNF-α-induced NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the role of initiator of innate immunity, HMGB1 also exerts an immunosuppressive effect through the T cell immunoglobulin domain and mucin domain 3 (TIM3), an immune checkpoint molecule on activated T cells [ 15 ]. Recently, we found that HMGB1 inhibitors, such as glycyrrhizin, exhibited an immunopotentiating effect in combination with an innate immunity receptor-related adjuvant in a murine peptide vaccine model [ 16 ]. These facts indicate that HMGB1 has two opposite functions, that is, it both initiates and suppresses immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, knockout (KO) of HMGB1 in the tumor cells using CRIPR/Cas9 suppressed in vivo tumor growth mediated by host CD8 T cells and accelerated infiltration of T cells as well as macrophages and dendritic cells (DCs) into the tumor tissues 21 . Our previous study 22 as well as others 23–25 regarding the anti‐tumor effect of HMGB1 inhibitors, suggested a possible application of suppression of tumor‐derived HMGB1 to cancer immunotherapy, such as ICB and neoantigen vaccine therapies 21–25 . Although most previous studies supported the negative effect of HMGB1 on anti‐tumor immunity, 21–25 a positive role of HMGB1 in the initiation of innate and subsequent adaptive immunity has also been shown 26,27 .…”
Section: Introductionmentioning
confidence: 98%